EVALUATION OF LAND FACILITIES AND MANAGEMENT OF PASSENGER AND VEHICLE CIRCULATION AT THE BANJARAYA RIVER PORT, BANJARMASIN CITY, SOUTH KALIMANTAN PROVINCE - Sari, Vita Permata; Agustina, Hera; Latuheru, Paulina M; Yulianto, Andri; Kartini, Marenetta (IWTJ : International Water Transport Journal, 2025)
The Banjaraya River Port is a link between the land transportation network of Banjarmasin City to Barito Kuala Regency which is separated by the Barito River. Currently, the condition of the Banjaraya River Port is not optimal due to a contract for 20 years, written in the lease agreement number 511/228/DPP/2004 dated September 10, 2004 between the Banjarmasin City Government and the Banjaraya Main Market Traders. This is contrary to the ideal condition of river and lake ports as stated in the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 40 of 2022 and the Decree of the Directorate General of Land Transportation Number SK.242/HK.104/DRJD/2010. The land facilities currently available at the Banjaraya River Port are the Banjaraya Terminal Building which functions as an administrative office, parking lot, canteen, ticket counter that has not been managed optimally, a traffic park and a post building that is not functioning and there is a market on the main road to the Banjaraya River Port. The research method used is mixed research by combining two methods, namely qualitative methods and quantitative methods. Based on the results of the analysis, the area needed for the terminal building is 283.2 m2 where there are 5 (five) rooms, namely the passenger waiting room (158.4 m2), canteen (23.76 m2), administration room (23.76 m2), utility room (51.48 m2) and public space (25.74 m2), it is necessary to reallocate passenger ticket counters before the waiting room and vehicles before the parking lot is ready to load. Dividing the functions of the available parking lot into a ready-to-load parking lot (48.6 m2) and a shuttle parking lot (118 m2). As well as managing the circulation of passengers and vehicles from the gate to the exit of the Banjaraya River Port using signs and markings.